(untitled) (Bangladesh Journal of Medical Science, 2023)
Background: TMA (Titanium-molybdenum) and SS (Stainless steel) wires are most commonly availed for orthodontic treatment. Meanwhile, patients are encouraged to employ mouthwashes containing fluoride to maintain their oral hygiene. Objective: To assess the effect of different fluoride prophylactic agents on TMA and SS wires for specific time periods namely 10 minutes, 1 hour, 24 hours. Material and Methods: The sample comprised TMA and SS wires immersed in agents such as Artificial saliva (pH = 6.8), Acidulated phosphate fluoride gel 1.23% and Stannous fluoride 0.4% to evaluate surface changes incorporated. 180 cut wires were used in this study; out of which half were SS and the other half were TMA wires. These wires were immersed for 10 minutes, 1 hour and 24 hours in each agent. Scanning electron microscope was also utilized to analyze the surface alterations. Results: The roughness of these wires increased after immersing in prophylactic agents. An increase in the surface roughness was found with SS wires in stannous fluoridesolution and APF gel on immersion at 10 minutes, 1 hour, and 24 hours’ time intervals with p-value being significant at 24 hour time in stannous fluoride. Conclusion: Orthodontists must avoid the contact of orthodontic wires containing titanium protective coating with prophylactic agents. Bangladesh Journal of Medical Science Vol.22 (Special Issue) 2023 p.47-51